PENERAPAN LESSON STUDY UNTUK MENINGKATKAN KOMPETENSI GURU DI SMA MUHAMMADIYAH 1 DAN SMA MUHAMMADIYAH 4 KOTA BENGKULU - Kasmiruddin Kasmiruddin; Endang Sulaeman (DHARMA RAFLESIA, 2018)
Changing the learning culture of teacher centered learning to student centered learning requires teachers to be able to choose a teaching method that is able to enhance the activity of students in learning. Based on observations, teachers in SMA Muhammadiyah 1 and 4 are generally still using conventional methods. This condition causes the students tend to be passive in the learning process, resulting in the average value of students in several areas of study under standard KKM of School. Besides, the school is less stimulating teachers to make innovations in learning. Forms of activity to be undertaken is the lesson study workshop for teachers in partner schools. Open lesson followed by reflection and evaluation of the implementation of lesson study workshop. Science and technology activities for the Community (IbM) which has been implemented can improve the knowledge and understanding of teachers about lesson study based learning. This activity can change the learning patterns from teacher centered learning to student centered learning. Thus an increase in activity of students and teachers in class. Keywords: Lesson Study, SMA Muhammadiyah 1 and 4, Bengkulu